Detection of Submicroscopic Soil-Transmitted Helminth Infections from Fecal Samples in Nangapanda, Ende, Using Real-Time Polymerase Chain Reaction - Maylasari, Roospita; Wulandhary, Sendy; Supali, Taniawati; Abinawanto, Abinawanto (UI Scholars Hub, 2014)
Soil-transmitted helminth (STH) infections (Necator americanus (hookworm), Ancylostoma duodenale (hookworm), and Ascaris lumbricoides) can lead to anemia, malnutrition, and iron deficiency. Traditionally, STH infections have been diagnosed using microscopy to detect eggs in human fecal samples. However, there are several limitations of this method. The aim of this research was to detect the percentage of submicroscopic STH infections from human fecal samples (children, 5–18 years old) in Nangapanda, Ende, using the real-time polymerase chain reaction (PCR) method. The fecal samples were collected in two time periods, which were before and after treatment, using 400 mg of Albendazole. There were 242 samples in total, but only 45 negative samples from microscopic detection were tested with real-time PCR. The DNA samples were isolated and amplified wih primers of internal transcribed spacer (ITS-1 and ITS-2) region of rDNA. The detection of samples with real-time PCR generated an amplification curve in VIC, FAM, and Texas Red fluorophore. Three samples (6.7%) in pre-treatment were low load of DNA (N. americanus and A. lumbricoides) (Ct > 35). Four samples (9.1%) were low load of DNA (N. americanus) (Ct > 35) in post-treatment. Five samples (11.4%) were moderate load of DNA (A. lumbricoides) (30 < Ct < 35) in post-treatment. This study showed that real-time PCR could detect submicroscopic infections from specific species of hookworm and A. lumbricoides